Electrocatalytic glycerol oxidation enabled by surface plasmon polariton-induced hot carriers in Kretschmann configuration. Issue 48 (29th November 2019) - Chung, Kyungwha; Zhu, Xingzhong; Zhuo, Xiaolu; Jang, Yu Jin; Choi, Chi Hun; Lee, June Sang; Kim, Seung-hoon; Kim, Minju; Kim, Kiheung; Kim, Donghyun; Ham, Hyung Chul; Baba, Akira; et al.
Abstract : Surface plasmon polariton-induced hot carriers facilitate glycerol electro-oxidation. Abstract : Plasmonic hot carrier generation has attracted increasing attention due to its ability to convert light to electrical energy. The generation of plasmon-induced hot carriers can be achieved via Landau damping in the non-radiative decay process of the plasmonic excitation energy. Localized surface plasmons (LSPs) undergo both radiative and non-radiative decays, while surface plasmon polaritons (SPPs) dissipate only via the non-radiative decay. Thus, it is a challenging task to exploit the surface plasmon polaritons for the efficient generation of hot carriers and their applications. In this study, a model hot-carrier-mediated electrocatalytic conversion system was demonstrated using an Au thin film in Kretschmann configuration, which is the representative platform to excite SPPs. AgPt-decorated Au nanobipyramids (AuNBPs) were designed and introduced onto the Au film, creating hot-spots to revolutionize the thin film-based photon-to-carrier conversion efficiency. The glycerol electro-oxidation reaction enabled by such SPP-induced hot carriers was evaluated and exhibited a photon-to-hot carrier conversion efficiency of 2.4 × 10 −3 %, which is ∼2.5 times enhanced as compared to the efficiency based on the neat Au film.